2023
DOI: 10.3389/fphar.2023.1043956
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of clinical research on dexmedetomidine in the past 2 decades: A bibliometric analysis

Abstract: Introduction: Dexmedetomidine is a potent, highly selective α-2 adrenoceptor agonist with sedative, analgesic, anxiolytic, and opioid-sparing properties. A large number of dexmedetomidine-related publications have sprung out in the last 2 decades. However, no bibliometric analysis for clinical research on dexmedetomidine has been published to analyze hot spots, trends, and frontiers in this field.Methods: The clinical articles and reviews related to dexmedetomidine, published from 2002 to 2021 in the Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Furthermore, we found that the protective effect of Dex on X-ray radiation-induced myocardial injury was through inhibiting autophagy. As Dex has been extensively used in clinical practice [ 52 ], our data may extend the possibility of using Dex for radiation-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, we found that the protective effect of Dex on X-ray radiation-induced myocardial injury was through inhibiting autophagy. As Dex has been extensively used in clinical practice [ 52 ], our data may extend the possibility of using Dex for radiation-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 70%
“…This drug has been introduced since 1999, and its effect on the pediatric population has been thoroughly studied. DEX can be used as a sedative agent in the intensive care setting, for procedural sedation, as an adjuvant, and even as a main anesthetic agent to babies and children undergoing surgical procedures [ 23 ]. The literature recommends an intravenous loading dose of 1 μg/kg within 10 minutes, followed by a maintenance dose of 0.7 μg/kg/hour.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine has been studied since 1999, and its use as a sedative agent for diagnostic procedures in intensive care units, as an adjuvant anesthetic, and even in painful procedures such as laryngoscopy has been well documented [ 16 , 18 22 ]. In fact, the majority of its studies were focused on the pediatric population [ 23 ]. Dexmedetomidine’s unique features are not comparable to other anesthetic drugs available.…”
Section: Introductionmentioning
confidence: 99%
“…The keywords were extracted from the keyword section of articles. To avoid potential deviations, similar or same keywords with different expressions were manually standardized to correct and/or group similarities as previously suggested[ 23 - 25 ], before VOSviewer or CiteSpace analysis. Burst keywords were assessed using CiteSpace (V6.2R4 SE) with the following parameters: time slicing (from January 1994 to December 2022), years per slice (1), node type (keyword), the minimum burst duration (1 year), γ (0.39) and others (default).…”
Section: Methodsmentioning
confidence: 99%